Chemically and electrochemically induced expansion and contraction of a ferrocene rotor1. Issue 38 (11th May 2015) - Scottwell, Synøve Ø.; Elliott, Anastasia B. S.; Shaffer, Karl J.; Nafady, Ayman; McAdam, C. John; Gordon, Keith C.; Crowley, James D.
<x xml:space="preserve">Abstract</x> A 2, 2′-bipyridine-appended ferrocene rotor can be switched, upon treatment with [Cu(CH3CN)4](PF6) and 6, 6′-dimesityl-2, 2′-bipyridine, from the stacked (syn) conformation to the unstacked (anti) conformation. The switching was completely reversible and could be triggered either chemically, or electrochemically.